Haunted Objects : Spectral Testimony in the Southern Cone Post-Dictatorship - Corbin, Megan (Book collections on Project MUSE., 2021)
"This book reconsiders a variety of material remainders from the past, in an effort to reveal the interpretive power that memory work in the present can gain from them: the everyday object of the detention center, the prison craftwork made as an important form of survival and resistance in the Chilean and Uruguayan detention centers, the personal items that belonged to the victim prior to his/her becoming victim, the bodies that emerge from mass graves, the bodies of the second generation that carry the material copies of the DNA of their disappeared parents, and the object that was once present at the scene of torture or detention and currently occupies the role of witness in the space of the museum"--